Influência da temperatura e umidade sobre as atividades de voo e sobrevivência de Melipona quadrifasciata Lepeletier, 1836 (Hymenoptera, Apidae, Meliponini) - Silva, Cristiane Pereira da (2019)
Bees are the main pollinating agents of native and cultivated angiosperm plants, helping to maintain biodiversity and providing benefits in food production and savings for humans. However, the increase in temperature caused by climate change contributes to other factors, such as the incorrect use of pesticides and the degradation of forest areas in the decline of several species of bees. In this context, it is necessary to understand how the increase in temperature due to climate change will affect pollinators and what the consequences will be in the face of these changes. Thus, the study aimed to determine the average lethal time and average lethal temperatures for species of stingless bees Melipona quadrifasciata Lepeletier, 1836, when exposed to high temperatures, and to investigate the influence of local temperature and relative humidity on the behavior of species foraging. For such purposes, the work was conducted at CCA - Center for Agricultural Sciences at the Federal University of São Carlos, in Araras - SP and subdivided into two stages: In the first stage, four temperatures were tested in the laboratory using BOD 26 (control) 30, 45 and 52ºC to determine the average lethal time (TL50) and lethal temperature based on the Prechet protocol established in 1973. Foraging and foraging activities and temperature measurements were observed and recorded in the dry and rainy seasons. and relative humidity of M. quadrifasciata colonies and the environment in a fragment of seasonal Semideciduous Forest from 8 to 18 hours. The results obtained show that in relation to the exposure to the average lethal time (TL50) and the average lethal temperature, the temperatures of 45 (1 day) and 52º C (5/24) had a worse performance when compared to the temperatures of 26 (34 days) 30ºC (29 days), for causing the mortality of 50% population in a period less than one day for the bee species M. quadrifasciata, thus having significant differences (P <0.05) between the treatments tested in the laboratory. For observations of foraging activity between seasons, a better performance of the dry season (F = 87.053, p <2e-16, p <0.001) was found when compared to rainy (F = 9.204, p 0.000115, p <0.001) in the numbers of entrances and exits bees differentiating from previous works, in which, the rainy season performs better than the dry season. Regarding the influence of the seasons on the collected material (pollen, nectar, other materials) and the disposal of garbage, it was observed that in the dry season the bees had a better performance in relation to the rainy season for all activities (p <0.001) . Another factor observed was the relationship between the behavior of the bees and the performance time of the activities that ran between 8 to 13 hours. Therefore, the work showed a positive result confirming that abiotic factors influence the survival and behavior of M. quadrifasciata. Finally, as a contribution to the study of the influence of abiotic factors on animal behavior, the results obtained can be used as a starting point for modeling and diagnostic studies on the damage and possible consequences of climate change in pollinators and on the availability of flowers and food for bees